Non-Traditional Management of the Neurogenic Bladder: Tissue Engineering and Neuromodulation - Jane M. Lewis; Earl Y. Cheng (The Scientific World Journal)
Patients with spina bifida and a neurogenic bladder have traditionally been managed with clean intermittent catheterization and pharmacotherapy in order to treat abnormal bladder wall dynamics, protect the upper urinary tract from damage, and achieve urinary continence. However, some patients will fail this therapy and require surgical reconstruction in the form of bladder augmentation surgery using reconfigured intestine or stomach to increase the bladder capacity while reducing the internal storage pressure. Despite functional success of bladder augmentation in achieving a low pressure reservoir, there are several associated complications of this operation and patients do not have the ability to volitionally void. For these reasons, alternative treatments have been sought. Two exciting alternative approaches that are currently being investigated are tissue engineering and neuromodulation. Tissue engineering aims to create new bladder tissue for replacement purposes with both “seeded” and “unseeded” technology. Advances in the fields of nanotechnology and stem cell biology have further enhanced these tissue engineering technologies. Neuromodulation therapies directly address the root of the problem in patients with spina bifida and a neurogenic bladder, namely the abnormal relationship between the nerves and the bladder wall. These therapies include transurethral bladder electrostimulation, sacral neuromodulation, and neurosurgical techniques such as selective sacral rhizotomy and artificial somatic-autonomic reflex pathway construction. This review will discuss both tissue engineering techniques and neuromodulation therapies in more detail including rationale, experimental data, current status of clinical application, and future direction.